(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
This study presents the assessment of the groundwater potential in Iyesi, Ota, southwestern Nigeria. Thirty (30) vertical electrical soundings (VESs) were conducted using Schlumberger array with a maximum half-current electrode spacing \((AB/2)\) of 420 m. The apparent resistivity data observed were interpreted first by partial curve matching and then by computer iteration technique using WinResist program. Eight eoelectric layers were denoted as top soil (sandy clay), lateritic clay, silty clay, silty sand, mudstone, medium grain sand, coarse sand and clay mud were delineated. The sixth (medium grain sand) and seventh (coarse sand) layers delineated form the aquifer unit with the overlying mudstone (fifth layer) serving as the confining bed. The geoelectrical and hydrogeological characteristics of the delineated aquifer in the study area was evaluated. The study shows that the aquifer is highly productive and consequently a good groundwater potential. The litho-facies of the aquifer units are well sorted and graded; this accounts for the observed decrease in the model resistivity with depth and thus, increasing porosity with depth in the aquifer unit.